Manajemen Risiko: Dampak Sosial Ekonomi dari Banjir pada Sawah di Kota Padang: Risk Management: Socio-economic Impact of Flooding on Rice Farming in Padang City - Paloma, Cindy; Mutiara, Vonny Indah (Journal of Integrated Agribusiness, 2025)
Flooding is a major natural disaster that substantially risks agricultural productivity, particularly rice cultivation. In Padang city, the severity of flood impacts has increased due to climate change. This study identifies and analyzes flood risk management strategies in paddy farming areas. The research used a descriptive approach supported by quantitative secondary data from government reports, insurance claim records, and climate-related publications. Data analysis involves risk mapping and descriptive statistics to assess patterns of flood impact and response strategies. The results indicate that effective flood risk management involves using flood-resistant rice varieties, constructing and maintaining irrigation and drainage systems, and participating in the Paddy Farming Insurance (AUTP). Risk Mapping shows that floods have the lowest impact compared to other floods or disasters. In Padang City, floods have not impacted 75% of AUTP insurance claims. Strategies that farmers and stakeholders can implement are preventive and mitigations. Preventive strategies include improving drainage systems and using flood-resistant crops, while mitigation involves early warning systems, weather forecasting, crop insurance, and post-flood management. However, barriers like insufficient funding, limited farmer awareness of technology, and poor infrastructure hinder adoption. Government support primarily benefit smallholder farmers-those most vulnerable to climate-related risk by offering technical assistance, financial subsidies, and encouraging AUTP participation. By implementing these strategies, agricultural resilience can be strengthened, contributing to national food security.